Systematics and phylogeny of the Neotropical Pachymenes de Saussure and Santamenes Giordani Soika (Hymenoptera, Vespidae, Eumeninae). (15th October 2014) - GRANDINETE, YURI C.; HERMES, MARCEL G.; NOLL, FERNANDO B.
Abstract The genera Pachymenes de Saussure and Santamenes Giordani Soika are revised and the phylogenetic relationships among their species, based on external morphology and male genitalia, are presented. The cladistics analysis, using 22 terminal species (19 ingroup and 3 outgroup species) and 44 characters, produced a single cladogram under implied weighting. Both genera were recovered as paraphyletic, althought two major clades were formed and were well supported by the re‐sampling analysis. We propose the synonymy of Pachymenes with Santamenes, and the description of two new species: P. saussurei Grandinete n.sp. and P. riograndensis Grandinete n.sp.. New combinations are: Pachymenes novarae (de Saussure) n.comb., P. olympicus (Zavattari) n.comb., P. peregrinus (Zavattari) n.comb. and P. santanna (de Saussure) revised combination. We state the synonymy of P. obscurus orellanoides under P. obscurus consuetus, reviewing the status of the latter and raising P. consuetus to species level. Pachymenes orellanae vardyi is synonymized under P. orellanae; P. ghilianii olivaceus, P. ghilianii flavissimus and P. peruanus are proposed as synonyms of P. ghilianii; P. picturatus obscuratus is synonymized under P. laeviventris; P. picturatus nigromaculatus and P. picturatus var. intermedia are synonymized under P. picturatus and P. atra var. ornatissima get its lectotype designated and proposed as synonym of P. ater. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:F1625D4F‐B9D0‐426D‐9140‐97E53A531F87.